Key Brainstem Structures Activated during Hypoxic Exposure in One-day-old Mice Highlight Characteristics for Modeling Breathing Network in Premature Infants - Joubert, Fanny; Loiseau, Camille; Perrin-Terrin, Anne-Sophie; Cayetanot, Florence; Frugière, Alain; Voituron, Nicolas; Bodineau, Laurence (Frontiers in Physiology, 2016)
We mapped and characterized changes in the activity of brainstem cell groups under hypoxia in one-day-old newborn mice, an animal model in which the central nervous system at birth is particularly immature. The classical biphasic respiratory response characterized by transient hyperventilation, followed by severe ventilation decline, was associated with increased c-FOS immunoreactivity in brainstem cell groups: the nucleus of the solitary tract, ventral reticular nucleus of the medulla, retrotrapezoid/parafacial region, parapyramidal group, raphe magnus nucleus, lateral and medial parabrachial nucleus, and dorsal subcoeruleus nucleus. In contrast, the hypoglossal nucleus displayed decreased c-FOS immunoreactivity. There were fewer or no activated catecholaminergic cells activated in the medulla oblongata, whereas approximately 45% of the c-FOS-positive cells in the dorsal subcoeruleus were co-labelled. Approximately 30% of the c-FOS-positive cells in the parapyramidal group were serotoninergic, whereas only a small portion were labelled for serotonin in the raphe magnus nucleus. None of the c-FOS-positive cells in the retrotrapezoid/parafacial region were co-labelled for PHOX2B. Thus, the hypoxia-activated brainstem neuronal network of one-day-old mice is characterized by i) the activation of catecholaminergic cells of the dorsal subcoeruleus nucleus, a structure implicated in the strong depressive pontine influence previously reported in the fetus but not in newborns, ii) the weak activation of catecholaminergic cells of the ventral reticular nucleus of the medulla, an area involved in hypoxic hyperventilation, and iii) the absence of PHOX2B-positive cells activated in the retrotrapezoid/parafacial region. Based on these results, one-day-old mice could highlight characteristics for modelling the breathing network of premature infants.